ANALISIS PENERAPAN PSAK NO. 16 TENTANG ASET TETAP PADA PT. BANK SULUTGO - Punusingon, Natalia; Sabijono, Harijanto; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2018)
In an operational company requires production factors to support the company in achieving its objectives. Of the several types of assets, there is one of the most important assets in supporting the company's operations, namely fixed assets. This study aims to find out that the company has implemented a fixed asset accounting policy that is appropriate and based on the Statement of Financial Accounting Standards (PSAK) no.16 in company activities. The method in this study is descriptive analysis method. In carrying out its accounting activities, PT. SulutGo Bank has referred to PSAK No. 16. In practice, companies distinguish types and ways of obtaining fixed assets with cash purchases or by establishing themselves, in depreciating fixed asset companies using the straight-line method and the declining balance method in accordance with applicable Accounting Standards, in terminating fixed assets whose useful lives has expired or is no longer used by removing assets from the register of ownership and releasing them through sales through auction. presentation and disclosure of assets in accordance with the pattern of financial standards and some information disclosed in financial statements. Keywords: fixed assets, SFAS no.16, financial statements, depreciating, financial accounting standard